Measurement of Geometric Variations of a Railway Truss Bridge (Case Study: BH77 Railway Bridge) - Anindhya Mustika Larasati; Pariatmono; Erlangga Rizqi F; Mawardi Amin; Resmi Bestari M; Dimas Aryo S; Mulyadi Sinung H; Dwi Agus P; Wimpie Agoeng N. A; Thiya Fiantika; Emeralda Insani. N. S. P. J. D. S. P (Majalah Ilmiah Pengkajian Industri, 2022)
Monitoring the condition of the railway track on a regular basis needs to be carried out regularly to minimize risk. One of the causes of the decrease in the strength of the bridge structure can be caused by changes in cross-sectional dimensions. The existing dimensions of the bridge structure need to be known because they will affect the steel frame profile area, where the steel frame area will affect the size or the small value of the deflection and stress of the bridge structure. The dimensions of the frame need to be seriously considered so that the stress and deflection values ??of the bridge structure remain constant. This research was conducted at the BH 77 Railway Bridge in Tegineneng, Tanjungkarang-Martapura, Lampung, which uses a type frame configuration warren truss. This location was chosen to fit the research that was also conducted by Badan Riset dan Inovasi Nasional (National Research and Innovation Agency of Indonesia). Based on the measurement of the dimensions of the bridge truss that has been carried out, the results show that there is a difference in the value of the circumference of each rod with the standard deviation for each similar profile. The biggest difference in the circumference of the truss is the profile of H beam, 113 and 115 rods with dimensions of 340×300×15×18, the initial circumference value is 1,280 mm, and after the measurement is 1,289.42 mm with a standard deviation value of 0.91 mm. while for the smallest difference, namely the H beam profile, rod 110 with dimensions of 340×310×39×21, the initial circumference value is 1,300 mm and after the measurement is 1,300.33 mm with a standard deviation value of 0.24 mm. Keyword: BH77 bridge, Bridge deflection, Bridge structure, Measurement geometry,  Railway bridges, Steel structure, Structural Health Monitoring System.